Femoral, Direct, and Rare Inguinal Hernias in Children—An Update - Gödeke, Jan; Muensterer, Oliver J. (European Journal of Pediatric Surgery, 2017)
Pediatric surgeons deal with inguinal hernias on a regular basis. While most of these are straightforward in terms of diagnosis and therapy, occasionally what initially sounds like a routine case turns out to be a perplexing conundrum. This review discusses rare and unusual findings in the groin area that may mimic an indirect inguinal hernia, but are not. To provide good and effective care, pediatric surgeons should be readily familiar with the possible differential diagnosis of these entities, along with their specific management. In general, laparoscopy is one of the most useful interventions to discern unusual groin pathology from standard indirect inguinal hernias and in many cases provides an effective treatment option at the same time.
Keywords: inguinal hernia; femoral hernia; direct hernia; groin pain; laparoscopy